2006
DOI: 10.1152/ajpregu.00280.2006
|View full text |Cite
|
Sign up to set email alerts
|

Human progenitor cells from bone marrow or adipose tissue produce VEGF, HGF, and IGF-I in response to TNF by a p38 MAPK-dependent mechanism

Abstract: Accumulating evidence suggests that progenitor cells may decrease destructive inflammation and reduce tissue loss by antiapoptotic mechanisms. However, they remain poorly characterized, and many questions remain regarding the mechanisms by which they may positively affect wound healing, tissue remodeling, or tissue regeneration. It has been speculated that various growth factors are responsible, but what components of the wound milieu stimulate progenitor cell production of growth factors and by what mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
174
1
15

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(198 citation statements)
references
References 45 publications
8
174
1
15
Order By: Relevance
“…MSCs have been widely studied and show great efficiency in clinical applications (Hong et al 2006(Hong et al , 2011. Previous studies have demonstrated that MSCs are able to produce various growth factors such as VEGF (Crisostomo et al 2007) and hepatocyte growth factor (Wang et al 2006) in vitro. These growth factors may promote angiogenesis (Wang et al 2006), decrease production of proinflammatory cytokines (Yang et al 2004(Yang et al , 2006 and reduce apoptosis (Ayala et al 1996(Ayala et al , 1998.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs have been widely studied and show great efficiency in clinical applications (Hong et al 2006(Hong et al , 2011. Previous studies have demonstrated that MSCs are able to produce various growth factors such as VEGF (Crisostomo et al 2007) and hepatocyte growth factor (Wang et al 2006) in vitro. These growth factors may promote angiogenesis (Wang et al 2006), decrease production of proinflammatory cytokines (Yang et al 2004(Yang et al , 2006 and reduce apoptosis (Ayala et al 1996(Ayala et al , 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that MSCs are able to produce various growth factors such as VEGF (Crisostomo et al 2007) and hepatocyte growth factor (Wang et al 2006) in vitro. These growth factors may promote angiogenesis (Wang et al 2006), decrease production of proinflammatory cytokines (Yang et al 2004(Yang et al , 2006 and reduce apoptosis (Ayala et al 1996(Ayala et al , 1998. However, MSC isolation from bone marrow remains a huge challenge and impedes their further development.…”
Section: Discussionmentioning
confidence: 99%
“…43 Moreover, ADSC secrete other potent growth factors, such as the vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), and growth factor-1, which is similar to insulin growth factor-1 (IGF-1). 44 The tumoral necrosis factor may significantly increase the secretion of VEGF, HGF, and IGF-1 of ADSC by the activation of p38, which is dependent on the protein kinase mechanism. 44 There are some molecular differences between ADSC and BMSC, although the profile of the expression of surface proteins [VII] and genes [VIII] appears to be similar 10,33 (Table 1).…”
Section: Dmem-lg-dulbecos's Modified Eagle's Medium)mentioning
confidence: 99%
“…44 The tumoral necrosis factor may significantly increase the secretion of VEGF, HGF, and IGF-1 of ADSC by the activation of p38, which is dependent on the protein kinase mechanism. 44 There are some molecular differences between ADSC and BMSC, although the profile of the expression of surface proteins [VII] and genes [VIII] appears to be similar 10,33 (Table 1). It is estimated that less than 1% of the genes are expressed differently by ADSC and BMSC.…”
Section: Dmem-lg-dulbecos's Modified Eagle's Medium)mentioning
confidence: 99%
“…The primary pathways involved in proinflammatory MSC signaling include the nuclear factor kappa-B (NF-kB), mitogenactivated protein kinase (MAPK) family, Jak=STAT, and Akt= PI3K pathways (25,48,145,148). Understanding the key components of these signaling pathways may allow targeted therapeutic interventions to promote antiinflammatory pathways while mitigating proinflammatory signals.…”
Section: Signaling Pathwaysmentioning
confidence: 99%